Environmentally relevant mixtures in cumulative assessments: An acute study of toxicokinetics and effects on motor activity in rats exposed to a mixture of pyrethroids - Starr, James M. (2012)
Due to extensive use, human exposure to multiple pyrethroid insecticides occurs frequently. Studies of pyrethroid neurotoxicity suggest a common mode of toxicity and that pyrethroids should be considered cumulatively to model risk. The objective of this work was to use a pyrethroid mixture that reflects human exposure to common pyrethroids to develop comparative toxicokinetic profiles in rats, and then model the relationship between brain concentration and motor activity. Data from a national survey of child care centers were used to make a mixture reflecting proportions of the most prevalent pyrethroids: permethrin, cypermethrin, β-cyfluthrin, deltamethrin, and esfenvalerate. The mixture was administered orally at one of two concentrations (11.2 and 27.4 mg/kg) to adult male rats. At intervals from 1 to 24h, motor activity was assessed and the animals were sacrificed. Pyrethroid concentrations were measured in the blood, liver, fat, and brain. After controlling for dose, there were no differences in any tissue concentrations, except blood at the initial time point. Elimination half-lives for all pyrethroids in all tissues were < 7h. Brain concentrations of all pyrethroids (when cis- and trans-permethrin were pooled) at the initial time point were proportional to their relative doses. Decreases in motor activity indicated dose additivity, and the relationship between pyrethroid brain concentration and motor activity was described by a four-parameter sigmoidal Emax model. This study links environmental data with toxicokinetic and neurobehavioral assays to support cumulative risk assessments of pyrethroid pesticides. The results support the additive model of pyrethroid effect on motor activity and suggest that variation in the neurotoxicity of individual pyrethroids is related to toxicodynamic rather than toxicokinetic differences.